Corporate governance, risk management and corporate performance : an investigation of the Nigerian banking sector - Mubaraq, Sanni (2012)
This thesis presents empirical evidence regarding the relationship among corporate governance, risk management and performance for a panel of 20 Nigerian banks over the period of 2006 to 2009. The study is based on quantitative and qualitative data collected from annual reports, financial databases, questionnaire and semi-structured interview. Statistical analysis such as correlation analysis, one-sample t- test and dynamic panel data regression models using the Generalized Methods of Moment (GMM) technique are employed to analyze the data and to seek support for the hypotheses. Qualitative interview based techniques were also employed to explain the quantitative results. Nine hypotheses and ten sub hypotheses are formulated based on two theories namely, agency theory and resource dependence theory. While some of the results were in line with theoretical expectations, others were found not to support the hypotheses formulated. Contrary to expectations, the study reveals that proportion of non executive directors on the board and directors' ownership was negatively significant in explaining corporate performance of banks. In addition, the study finds that interest-rate risk was statistically insignificant in explaining the accounting performance of banks. Furthermore, the study reveals that three corporate governance variables representing board size, proportion of non executive directors on the board, and ownership concentration were not significant in explaining the impact of financial risk on these variables. The study also finds a positive relationship between government ownership and credit risk on one hand and negative association between government ownership and both interest rate risks and liquidity risks respectively, on the other. Hence the results for the relationship between government ownership and financial risks are inconclusive. Overall, the study revealed supervisory deficiencies on the enforcement of corporate governance and risk management of banks as banks have not yet fully complied with corporate governance codes and risk managements framework. The study also shows that the regulatory approach/tools to risk management practices of these banks have been fairly average, indicating that more still need to be done to enhance sound risk management practices in these banks. The results of the study have both theoretical as well as policy implications. In terms of theoretical implications, the two theories used in this study (i.e., agency theory and resource dependence theory) were each partially supported by findings of the study. Thus, this adds further to the fact that no single theory can explain the nexus of governance and performance. In terms of policy implications, the fact that some corporate governance and risk factors are unable to enhance banks performance, even after the enactment of mandatory codes of corporate governance specifically meant for the banking sector, pose some regulatory questioning. Hence, the need for regulatory agencies to be more proactive in enforcing the codes to achieve the desire goals for which the codes are enacted. As detailed in the study, this thesis contributes to theory and practices in terms of knowledge, policy and regulation.